FENOMENA KEHILANGAN ENERGI PADA PIPA MENGGUNAKANPENDEKATANMODEL FISIK SKALA LABORATORIUM - Imam Suprayogi; Bochari -; Joleha - (Jurnal APTEK, 2014)
The main purpose of this research is doing a review of inpipe energy loss using a laboratory-scalephysical model approach to establish the graphic of relation pattern between friction factor (f) toReynoldsNumbers (Re) and also the graphic of relation pattern between pressure height (h) to the stream’svelocity (v).This research used a laboratory-scale physical model approach. The instrument used wasPipeFrictionApparatus which equipped withHydraulicBenchmade by ArmfieldInc., USA in 2006.The main resultproved that the amount of in-pipe energy loss (hf) was highly influenced by the friction coefficientparameter (f), pipe diameter (D), pipe length (L) and also the velocity of in-pipe stream (v). The secondaryresult showed the type of stream in this laboratory-scale research was a turbulence one.